A role played by the All-Union Communist Party (Bolsheviks) Central Committee Bureau for Lithuania in suppressing resistance of partisans (November 1944–March 1947) - Pocius, Mindaugas (Genocidas ir rezistencija, 2018)
By a decision of the Organisational Bureau of the All-Union Communist Party (Bolsheviks) Central Committee, Mikhail Suslov was dismissed as chairman of the ACP(B) CC Bureau for Lithuanian Affairs and appointed a member of the Organisational Bureau, which had an impact on changes in the distribution of power within the Communist Party of Lithuania and in its relations with Moscow. The changes in the composition of the Bureau for Lithuanian Affairs in the summer of 1946 affected the organisation of the fight against the guerilla movement, which was gradually taken over by the professional security officers of the centre.